Assessment of the Pollution of Soils Utilized for Growing Edible Plants in the DR Congo - Mpanga, Fabien Ilunga; Lutandula, Michel Shengo (The Global Environmental Engineers, 2022)
This research was carried out with the aim to assess the pollution that threatens agricultural soils in urban areas in the Haut-Katanga region (DR Congo) by searching for heavy metals in the arable soil bordering the Kimpulande drain, in the nearby of the Shituru commune, the City of Likasi. This drain has been utilized since the 1930s by the Gécamines, the largest state-owned mining company in the country, to dispose of wastewaters from the copper and cobalt industry. The population living in Shituru utilizes the arable soil bordering the Kimpulande drain to grow edible plants. Based on the results from physicochemical analysis of soil samples from the first 40 centimeters and the determination of the spatial distributions of pH, electrical conductivity, and concentrations of selected heavy metals (Cu, Co, Cd, and Fe), it was concluded that the study area is composed of an alkaline soil (pH = 7.54) of which the average electrical conductivity is about 700 µS/cm. Unlike average concentrations of cobalt and iron, those of copper and cadmium have similar behavior, given that their average values decrease with soil depth. Besides, the soil utilized for urban agriculture of edible plants is polluted on the surface by cadmium (> 3 mg/kg) and copper (> 40 mg/kg). It is contaminated in depth by cadmium (> 1 mg/kg) and cobalt (from 20 up to more 100 mg/kg). This is not the case for copper and iron, given that their concentrations remained smaller compared to the limits set by the quality standards (QS) applicable to soils for agricultural use. Given the toxicity related to the presence in the arable soil of heavy metals to high concentrations, it was deduced that the Shituru in-force agricultural practices might result in the population’s exposure to serious health problems. Consequently, the urban agriculture of edible plants on arable soils threatened by mineral pollution must be prohibited to protect the population’s health.